ARAP1 fine-tunes F-actin polymerization level in lymphocytes through RhoA inhibition - Ueda, Yoshihiro; Kondo, Naoyuki; Kamioka, Yuji; Kinashi, Tatsuo (Frontiers in Immunology, 2025)
Rho family of small GTPases play crucial roles in F-actin polymerization and actomyosin contractility, facilitating lymphocyte polarization, motility, and adhesion. However, the spatiotemporal cooperation of these processes remains unclear. In this study, we found that the dual GTPase-activating protein (GAP) ankyrin repeat and PH domain 1 (ARAP1) modulates RhoA activity through its Ras-association (RA) domain, which binds to Rac and Rap1 and is critical for F-actin polymerization and cell migration. ARAP1 was transiently recruited to cell protrusions following chemokine stimulation. ARAP1-deficient cells exhibited enhanced chemokine-directed migration, accompanied by increased RhoA activation and F-actin polymerization. Conversely, ARAP1 overexpression had the opposite effect and inhibited migration in a manner dependent on its RhoGAP domain. Notably, the RA domain bound Rap1 and Rac1 and was required for ARAP1-mediated RhoA inhibition. These findings indicate that ARAP1 modulates RhoA activity at Rac/Rap1-rich protrusions and fine-tunes F-actin polymerization and cell motility.